Edukasi Transformasi Fisik Dan Psikologis Pada Masa Aqil Baligh Di Desa Sumbernongko Kecgusikan - Machnunah Ani Zulfah; Firman Al Azizi; Raya Agung Wirayudha; Devi Eka Putri Rahmadyani; Himanlah Azifah; Kartika Sari; Nur Aina Aini Faizzatu Saidah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2026)
Puberty is a developmental phase characterized by physical, psychological, social, and spiritual changes that require adequate understanding for adolescents to adapt positively. However, education regarding puberty within *Taman Pendidikan Al-Qur'an* (TPQ—Quran Education Center) settings remains relatively limited, leaving many students without a clear understanding of the changes occurring within them. This community service initiative aimed to analyze the implementation of an educational program concerning the physical and psychological changes associated with puberty and to assess its impact on improving the understanding of TPQ students in Sumbernongko Village, Ngusikan District, Jombang Regency. The results indicate that prior to the program, the majority of participants possessed limited knowledge regarding the physical and psychological changes associated with puberty. Following an educational seminar supported by learning aids such as pocketbooks and posters, participants demonstrated an improved understanding of the concept of puberty, the signs of physical and psychological changes, and the accompanying religious responsibilities. Furthermore, participants responded positively to the activities and considered the provided material relevant to their needs. Future community service initiatives are encouraged to involve a larger number of respondents and employ quantitative or mixed-methods approaches to measure program effectiveness more comprehensively.